Potensi Ikan Barbir (Pethia conchonius) dan Lemon (Labidochromis caeruleus) Jantan dan Betina sebagai Predator Biologis Larva Nyamuk Aedes aegypti - Hebert Adrianto; Etha Rambung; Natalia Christiani (Jurnal Kesehatan Andalas, 2022)
Fish as natural predators of mosquito larvae is a way of controlling mosquito larvae biologically that does not pose a risk to the health of organisms and environmental damage and overcoming the problem of mosquito resistance to chemical larvacide. One fish tested in the study was the rosy barb (Pethia conchonius) and lemon cichlid (Labidochromis caeruleus). Objectives: To analyzed  a difference in the predation ability of male and female fish to the larvae. Methods: This was an experimental study in the laboratory with a post-test-only design and five replications. One aquarium contains one liter of water, one fish, and 25 larvae of Ae. aegypti. Fish testing starts in the afternoon at 15.00 WIB. Observation the predation time of the fish until the fish eat all the larvae. Results: The average predation time of male P. conchonius fish was 1.57 minutes, and the female was 76.05 minutes. The average predation time of male L. caeruleus fish was 36.72 minutes and for females, 22.08 minutes. There was a significant difference between the predation of the male and female P. conchonius fish groups. There was no significant difference between the predation of male and female L. caeruleus fish groups to Ae. aegypti larvae. Conclusion: Rosy barb (P. conchonius) and lemon cichlid (L. caeruleus) have the potential to control the larval population of the Ae. aegypti mosquito. Rosy barb male has faster predation ability than other fish.Keywords:  Aedes aegypti, female, Labidochromis caeruleus, Pethia conchonius, male